Rethinking political humor: a dialogical analysis of social media in Turkey - Cöbek, Gözde. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
This thesis aims to explore the nature of political humor and its relation to politics through a dialogical analysis of three online political humor pages on Facebook which differentiate themselves from each other within the humor field by taking different positions, and of their engagement with politics in Turkey. Following the phenomenological approach and Ranciere’s theory of the distribution of the sensory/sensible as a theoretical framework, this study understands political humor as a specific political and aesthetic worldview of a particular group, as a particular mode of constructing, perceiving and sensing the social world which in fact stems from the distribution of the sensible. In this regard, Barthian semiotic analysis of these three different online political humor pages demonstrates how political humor as a political and aesthetic discourse is both subversive in terms of exposition of the state’s role in determining, constructing, shaping and regulating the individuals’ sensibility and perceptibility, their imagination, and reproductive in terms of reproduction of their imagination constructed and shaped by the state. By showing the contradictory nature of political humor, this thesis argues that in contrast to the main sociological understanding of humor as a form of resistance, political humor functions not merely as a weapon against the state and its distribution of the sensory, but also as a means of reproduction of that very distribution of the sensible, and that it is in essence intrinsic to the distribution of the sensory.
Keywords: Politicians -- Wit and humor.; Wit and humor -- Political aspects -- Turkey.; Social media -- Political aspects -- Turkey.